Human CYP enzyme-activated genotoxicity of 2, 2′, 4, 4′-tetrabromobiphenyl ether in mammalian cells. (March 2022) - Song, Meiqi; Wang, Yujian; Chen, Zhihong; Gao, Hongbin; Yang, Zongying; Yu, Hang; Liu, Yungang
Abstract: Polybrominated biphenyl ethers (PBDEs) are a group of persistent organic pollutants with endocrine-disrupting, neurotoxic, tumorigenic and DNA-damaging activities. They are hydroxylated by human liver microsomal CYP enzymes, however, their mutagenicity remains unknown. In this study, 2, 2′, 4, 4′-tetrabromobiphenyl ether (BDE-47, relatively abundant in human tissues) was investigated for micronuclei induction and DNA damage in mammalian cells. The results indicated that BDE-47 up to 80 μM under a 6 h/18 h (exposure/recovery, covering 2 cell cycles) regime did not induce micronuclei in V79-Mz and V79-derived cell lines expressing human CYP1A1 or 1A2, while it was moderately positive in human CYP2B6-, 2E1-and 3A4-expressing cell lines (V79-hCYP2B6, V79-hCYP2E1-hSULT1A1 and V79-hCYP3A4-hOR, respectively). Following 24 h exposure, BDE-47 induced micronuclei in V79-hCYP2E1-hSULT1A1 and V79-hCYP3A4 cells at increased potencies. In the human hepatoma (HepG2) cells BDE-47 (48 h exposure) was inactive up to 40 μM, however, pretreatment of the cells with ethanol (0.2%, v:v, inducer of CYP2E1) or rifampicin (10 μM, inducer of CYP3A4) led to significant micronuclei formation by BDE-47; pretreatment with bisphenol AF (100 nM) also potentiated BDE-47-induced micronuclei formation (which was blocked by a CYP2E1 inhibitor trans -1, 2-dichloroethylene or a CYP3A inhibitor (ketoconazole). Immunofluorescent staining of centromere protein B with the micronuclei formed by BDE-47 in HepG2 cells pretreated with ethanol or rifampicin demonstrated selective formation of centromere-containing micronuclei. The increased phosphorylation of both histones H2AX and H3 in HepG2 by BDE-47 also indicated an aneugenic potential. Therefore, this study suggests that BDE-47 is an aneugen activated by several human CYP enzymes. Graphical abstract: Image 1 Highlights: 2, 2′, 4, 4′-Tetrabromobiphenyl ether (BDE-47) is aneugenic in mammalian cells. The aneugenicity of BDE-47 depends on metabolic activation by human CYP enzymes. Human CYP3A4 and 2E1 might be the major enzymes activating BDE-47.